Degradation of direct red 23 dye in a plug flow reactor with adjustable angle baffles using nano-Fe3O4 modelling and optimisation - Zoqi, Mohamad Javad (Environmental technology, 2024)
Photocatalytic degradation is a key technique in wastewater treatment, particularly for toxic dye removal, yet challenges related to poor hydrodynamics and mass transfer limitations persist. This study addresses these challenges by innovatively employing an adjustable-angle baffle in a plug flow reactor (PFR) to enhance dye removal efficiency. A lab-scale PFR with an adjustable baffle was utilised to assess the impact of various factors, including baffle angle, catalyst concentration, hydraulic retention time (HRT), pH, and initial dye concentration, on the removal of direct red 23 dye. The experimental design employed a central composite design (CCD), with subsequent data analysis using response surface methodology (RSM) and artificial neural network (ANN) models. The findings demonstrate that the adjustable baffle significantly impacts dye removal, achieving maximum efficiency at an optimal angle of 77.5 degrees. The ANN model outperformed the RSM model, with a higher determination coefficient (R2) of 0.994 compared to 0.928. Furthermore, RSM and genetic algorithms yielded closely aligned optimal conditions, validating their accuracy. The optimised conditions achieved a dye removal efficiency of 89.47%. Significantly, the study also identified degradation as the dominant mechanism over adsorption and highlighted the impressive stability of nano-Fe3O4 during the recycling process. Mineralisation analysis revealed the presence of lightweight organic residual molecules post-treatment. These outcomes demonstrate the effectiveness of adjustable baffles in PFRs, marking a significant advancement in wastewater treatment technologies and underscoring the critical role of baffle orientation and catalyst concentration in optimising dye removal processes